ANALISIS KETERAMPILAN PROSES SAINS DAN KETERAMPILAN KOGNITIF SISWA MELALUI METODE PRAKTIKUM BIOLOGI PADA SUB MATERI SCHIZOPHYTA DAN THALLOPHYTA - M. Rezeki Muamar; Rahmi Rahmi (FKIP, 2017)
The aims of the research are to analyze the science process skills and cognitive skills of students through practical activities in learning Schizophyta and Thallophyta. The research was conducted at SMA Negeri 1 Peusangan Selatan.Â The research is a quantitative and descriptive quantitative research. The population in this study was 30 students. Total sampling method was used in this study. Three instruments were used in this study, namely observation sheet, test, and questioner. Data were analyzed using descriptive analysis and inferential analysis. The results showed that the students have good science process skills. Furthermore, the results also proved that there is positive effect of using practicum methods in learning Schizophyta and Thallophyta toward students understanding in Schizophyta and Thallophyta concepts. In addition, the research demonstrated the positive perspective in learning Schizophyta and Thallophyta concepts trough practicum methods.